1999
DOI: 10.1002/(sici)1096-8652(199903)60:3<175::aid-ajh1>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma tissue factor pathway inhibitor in women taking combined oral contraceptives

Abstract: Use of combined oral contraceptives (OC) is associated with a significant risk of thrombosis. The mechanisms of this effect are not clearly defined. Tissue factor pathway inhibitor (TFPI) is a circulating anti-coagulant that inhibits the earliest steps in activation of the extrinsic coagulation pathway. It plays a central role in control of coagulation but its contribution to the thrombotic risk associated with OC has not been assessed. Plasma TFPI antigen and activity, factor VIIa, prothrombin fragments 1&2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 29 publications
(29 reference statements)
4
38
1
Order By: Relevance
“…TFPI is cleared from the circulation by the liver and kidneys [32]. The decrease in free TFPI induced by oral contraceptives might be caused by changes in synthesis, clearance or lipoprotein profile [30,34].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…TFPI is cleared from the circulation by the liver and kidneys [32]. The decrease in free TFPI induced by oral contraceptives might be caused by changes in synthesis, clearance or lipoprotein profile [30,34].…”
Section: Discussionmentioning
confidence: 95%
“…Concerning TFPI, other studies observed that oral contraceptives lower TFPI activity, and free and total antigen [9,30].…”
Section: Discussionmentioning
confidence: 99%
“…There are anecdotal reports of the disappearance of bleeding symptoms during treatment, with normalization of vWF and FVIII levels in several cases [48]. A significant increase in FVIII and vWF levels in normal women on oral contraception has been shown in some but not all studies [31,[49][50][51]. However, the hemostatic effects are variable with markedly elevated clotting factor levels in some individuals [50].…”
Section: Oral Contraceptivesmentioning
confidence: 99%
“…TFPI binds directly and inhibits the earliest steps in extrinsic pathway activation by binding factor Xa (which involved in the activation of prothrombin to thrombin) and tissue factor (TF)/factor VIIa complexes in an inactive quaternary complex (30). Low plasma TFPI levels have been reported in patients with ischemic stroke (31), thrombotic thrombocytopenic purpura (32), and in women taking combined oral contraceptives (33).…”
Section: Introductionmentioning
confidence: 98%